Implementation of Problem Based Learning (PBL) Learning Model on Literacy Ability - Nurhayati, Nunung (Jurnal PGSD, 2023)
Currently, education in Indonesia has a relatively low ranking compared to other countries in terms of the education system. There are several reasons why education in Indonesia is still low compared to other countries. One of them is the influence of a lack of literacy or interest in reading on students. The purpose of this study is to describe the results of research on the implementation of the Based Learning model on literacy skills. These findings are then used as a basis for looking for new ways, especially the benefits of the PBL model in increasing basic education literacy skills. The research method uses content analysis of the 2018-2022 articles from Google Schoolar, Scopus.com and Garuda websites which are searched using the keyword "PBL". The research findings show that the PBL learning model can improve literacy skills. The new way is in the form of the benefits of implementing the PBL model in improving literacy skills, including: PBL is useful for training students in problem solving, obtaining knowledge or key concepts from the material, training critical thinking skills, increasing scientific literacy, constructing their own knowledge, growing motivation and self-confidence in learning, improve communication and work together in groups and can facilitate student involvement. Based on this research, PBL increases student literacy in several ways such as developing critical thinking skills, problem solving abilities, communication skills, ability to connect theory with concepts, increasing motivation which influences the willingness to learn further and student involvement in the learning process which ultimately can improve literacy.